2019
DOI: 10.1161/circinterventions.118.006823
|View full text |Cite
|
Sign up to set email alerts
|

Patient Body Mass Index and Physician Radiation Dose During Coronary Angiography

Abstract: Background: Consistent with the increasing prevalence of obesity in the general population, obesity has become more prevalent among patients undergoing cardiac catheterization. This study evaluated the association between patient body mass index (BMI) and physician radiation dose during coronary angiography. Methods and Results: Real-time radiation exposure data were collected during consecutive coronary angiography procedures. Patient ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(35 citation statements)
references
References 20 publications
3
31
1
Order By: Relevance
“…We also did not obtain the patients' body mass index as an influencing factor of radiation exposure, which is influencing the radiation exposure mainly in diagnostic and interventional imaging of the thorax and abdomen, but has a minor influence in head and neck procedures [23]. On the other hand, Miller et al suggested to establish reference levels in interventional neuroradiology without a weight correction [10].…”
Section: Limitationsmentioning
confidence: 97%
See 1 more Smart Citation
“…We also did not obtain the patients' body mass index as an influencing factor of radiation exposure, which is influencing the radiation exposure mainly in diagnostic and interventional imaging of the thorax and abdomen, but has a minor influence in head and neck procedures [23]. On the other hand, Miller et al suggested to establish reference levels in interventional neuroradiology without a weight correction [10].…”
Section: Limitationsmentioning
confidence: 97%
“…Likewise, fluoroscopy time increased per each additional thrombectomy attempt and was significantly different when comparing EST with one or two thrombectomy attempts (median (IQR), in minutes; FT 1 , 16 (11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) and FT 2 , 26 (21-41), p value 0.001). An additional third, fourth, or fifth thrombectomy attempt led to a significant increase (FT 3 , 35 min (25-45), p value 2vs3 0.008; FT 4 , 49 min (32-76), p value 3vs4 0.0003; and FT 5 , 67 min (57-98), p value 4vs5 0.005).…”
Section: Primary Analysismentioning
confidence: 98%
“…3) the current angulation of the integrated system, which is consisted of the X-ray tube and the detector, in relation to the central axis of the patient's table -in multiple planes; 4) the current position of the patient table -which can be moved vertically (up and down) as standard, and depending on the model of the device -horizontally and angularly; 5) weight and height of the patient [51,52]; 6) geometric scheme that corresponds to the operator's room arrangement (the solution stipulates that it is necessary to have appropriate, clearly visible markings on the floor, in accordance with the scheme, which indicate where the staff should be positioned (several options, considering the type of procedure and mentioned internal planning decisions); 7) operator heights (correspond to the geometric scheme: the basic, minimum number of operators provided for certain medical procedure are processed) [53]. Information on the distribution of scattered radiation for all reference points and all angulations is defined before clinical work and the corresponding values are changed only in case of inconsistency, after off-schedule or regular dosimetric examinations, whereby a control set of measurements would determine the necessity to complete measuring process.…”
Section: Protective Screen Integrated With C-arm X-ray Devicementioning
confidence: 99%
“…RE in EST might differ between different stroke centers as angiography units and thrombectomy technique differ as well. Patient's anatomic variants and bodies (including body mass index; no-necked, short-necked, and long-necked patients) are not considered in this study [19,20]. If this plays a role in the differing EST of the anterior and posterior circulation remains uncertain until further investigation.…”
Section: Limitationsmentioning
confidence: 99%